SCHIZOPHRENIFORM IN ANDRES HEINZ’S BLACK SWAN - Juni Zarlina (LINGUA LITERA : journal of english linguistics and literature, 2021)
Abstract This research aims to analyze the personality disorder, Schizophreniform, that happened in this drama, Black Swan by Andres Heinz. It describes that the maincharacter, Nina Sayers, has a psychological problem. She suffers from Schizophreniform. Three questions appear to discuss i.e. the causes, the symptoms, and defense mechanism of Schizophreniform perceived by Nina Sayers the main character. This research uses a theory of Psychoanalysis by Sigmund Freud. There are two concepts to be applied to three problems in this research. The concepts are Id, Ego & Superego, and Defense Mechanism. These concepts help this research to describe the symptoms and the defense mechanism of Schizophreniform. The result of this research found that Nina Sayers shows the symptoms of Schizophreniform after experiencing the stressful event to be a new swan queen in the prestigious ballet company and poor social interaction as the causes of Schizophreniform. The symptoms are visual hallucinations and delusions. Then, the Defense Mechanisms of Schizophreniform that appear in this drama are identifications and Introjections.